A Pathophysiological Model for COVID-19: Critical Importance of Transepithelial Sodium Transport upon Airway Infection. Issue 2 (6th October 2020) - Gentzsch, Martina; Rossier, Bernard C
Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic remains a serious public health problem and will continue to be until effective drugs and/or vaccines are available. The rational development of drugs critically depends on our understanding of disease mechanisms, that is, the physiology and pathophysiology underlying the function of the organ targeted by the virus. Since the beginning of the pandemic, tireless efforts around the globe have led to numerous publications on the virus, its receptor, its entry into the cell, its cytopathic effects, and how it triggers innate and native immunity but the role of apical sodium transport mediated by the epithelial sodium channel (ENaC) during the early phases of the infection in the airways has received little attention. We propose a pathophysiological model that defines the possible role of ENaC in this process.